Beta contábil X Beta CAPM: um estudo com as empresas dos setores regulados e não regulados listados na BM&FBovespa - Moreira, Márcio Lima (2013)
Considering that accounting information plays an essential role for investors and might provide a valuable helping hand in risk assessment, this study has the general objective of verifying whether the risk parameter estimated by accounting variables (Accounting Beta) are related to the market risk assessment (Market Beta) of companies listed by BM&FBovespa. In addition, the study aims at checking whether there is any difference between accounting beta and market beta in companies from regulated and nonregulated sectors while taking into consideration that companies in regulated sectors present specific norms for disclosure, which suggests a higher information level and lesser risk, which consequently affects these companies’ accounting beta and market beta. The study comprehends all companies listed by the Bolsa de Valores, Mercadorias e Futuros (BM&FBOVESPA) or BOVESPA Commodities and Futures Exchange on October 26th 2013, summing up to 528 (five hundred and twenty eight) companies from various listing segments. Out of the 528 companies, holdings and companies whose data were not available at the sampling period were left out. Therefore, the final research sample comprehends a total number of 221 companies, out of which 53 are regulated sector companies and 168 are non-regulated sector companies. Besides the sampling of data from BM&FBovespa sites and from the Comissão de Valores Mobiliários (CVM), the Economática data bank was employed as a source. This study has used the normality test, the average difference test, Spearman’s correlation analysis, and regression analysis. Results have indicated that only companies from non-regulated sectors presented relation between CAPM Beta and Accounting Beta. On the other hand, in companies from regulated sectors a different result was observed, in which no relation was identified between the two indexes. In general, after assessment of the total sample of companies, which included regulated and non-regulated companies, results point at an absence of relation between CAPM Beta and Accounting Beta. One of the research hypotheses was not confirmed.